Spatial and temporal distribution and potential residency of bottlenose dolphins (Tursiops truncatus) off São Miguel Island, Azores - Catalão, Rita (2021)
The common bottlenose dolphin (Tursiops truncatus) is a cosmopolitan cetacean species distributed all over the world, except in the poles. This species is also one of the most sighted in the island of São Miguel, Azores, however it is still poorly studied. This thesis describes the spatial and temporal distribution of bottlenose dolphins sighted off São Miguel and presents a catalogue with the individuals identified between 2014 and 2019. Furthermore, their degree of residency around the island of São Miguel is also assessed. Data was collected using as opportunistic platforms of observation the whale watching boats of Futurismo Azores Adventures, a company with main base port in Ponta Delgada, on the south of the island. Two datasets were used: the first includes the information from the bottlenose dolphin sightings registered between 2010 and 2019, and it was used to analyse spatial and temporal distribution of bottlenose dolphins around the island; the second dataset includes pictures taken during the whale watching trips from 2014 until 2019, and it was used to build a catalogue with the individuals identified during that period, look for residency patterns and associations among the residents. The results revealed a preference for shallower waters indicating a higher number of sightings in depths lower than 500m. The presence of bottlenose dolphins varied between seasons and inter-annually, with higher occurrences during the warmer months. This pattern has been seen in other studies and it could be related to higher concentration of prey after a peak in phytoplankton in the previous months. From the 505 individuals identified only 52 dolphins were considered residents. Within these dolphins there were four possible associations between several individuals based on the dates they were encountered on. This study is the first to present a catalogue with individuals from São Miguel and one of the first to analyse the spatial and temporal distribution of bottlenose dolphins in the island. Further research would be needed to contribute to the overall knowledge of this species in São Miguel and support proper management and conservation plans for the species in this area.